Sustainability and Energy Management Innovative and Responsible Business Practices for Sustainable Energy Strategies of Enterprises in Relation with CSR - Weber, Gregor (Sustainable Management, Wertschöpfung und Effizienz,, 2018)
In this book Gregor Weber deals with enterprises and the pool of challenges including energy efficiency and sustainability they are confronted with. His research results in a two level model supporting enterprises on innovative and responsible business practices. It was awarded with the "Project Sustainability 2017" by the Council of Sustainable Development of the German government as well as with the "German Industry Award 2017". Contents Current tendencies regarding energy economics effects and the relevance of sustainable energy KIBS (Knowledge Intensive Business Services) in this context Present approaches in sustainable energy economics and innovation in relation to CSR (Corporate Social Responsibility) Studies regarding strategies of enterprises dealing with the evolution of the energy sector and innovative and responsible business practices for sustainable energy Proposals of business models for innovative and responsible energy strategies and social responsibility Target Groups Lectures and students of management, energy efficiency and sustainability Professionals in management, CSR and environmental management The Author Dr. Gregor Weber is founder & CEO of the ecoistics.institute and founder of the UN-world decade initiative on sustainability ACT-ORANGE. He benefits from an extensive international experience as management consultant, lecturer, moderator, author and researcher in the field of energy and sustainability economics and was awarded several times.